Perancangan Jumlah Karyawan Berdasarkan Beban Kerja Operator - Yusuf Mauluddin; Hemas Pramesti (Jurnal Kalibrasi, 2026)
The operator workload problem is a problem in the Heat Treatment production department. The disparity between the amount of work done by the operator and the number of operators per shift is 3 people working in teams, if one operator does the loading process and the other operator does the cleaning to carry out the heat treatment process on a different machine. The work performed does not stop and will be repeated continuously on the Heat Treatment operator with a total of 10 materials within 2 hours for one Heat Treatment process. The purpose of writing this thesis is to identify the workload of Heat Treatment operators at PT Dirgantara Indonesia and get improvements and design the number of Heat Treatment operators at PT Dirgantara Indonesia. In completing this case study, the author uses the Nasa-TLX method which is a method used to see how much mental work employees have to do to do different things at work, then will be completed using the FTE method which is a method used to know the level of mental workload so that improvements will be made by adding operators. So that the final result of the preparation of this thesis is to find out about work productivity after the addition of operators.